Wear a mask to reduce COVID-19 transmission while exercising at the gym: belief or evidence-based? (Research, Society and Development, 2020)
Introduction: After the spread of new coronavirus (COVID-19) around the world, some sanitary measures were adopted to reduce the transmission rate. Social distancing and the use of masks are one of them. Therefore, after months of pandemic situation, levels of infection and mortality began to decline in some regions of Brazil. As a result, some states and municipalities started to relax their quarantines allowing access to some community places like gyms. To access these places is obligatory the use of masks. However, there is a lack of knowledge about the efficiency of the use of masks in closed environments, particularly in situations with increased production of body fluid, like in physical exercise.Objective: To overview the use of masks and the inefficiency in reducing the transmission risk of new coronavirus during physical activity practice at gyms.Conclusion: Despite the extreme necessity of using masks to reduce the risk of COVID-19 transmission, there is no evidence of its efficacy in closed environments during physical exercise so far. In addition, the use of masks negatively affect the performance of physical activity. The only plausible requirement in the current pandemic context would be to present the COVID-19 test result to practice activity indoors.